Design of a Control System for Greywater Collection and Reuse in Toilet Tanks - Payano Atoc, Branco Victor (2024)
A very concurrent problem is the water scarcity that is growing day by day because many of us misuse water resources. Therefore, this research has an alternative solution which is the reuse of greywater (GW) which is extracted from hand washers, showers, and washing machines, which will go through a process of filtering and disinfection using UV rays for subsequent reuse through an automated ON-OFF control system. In this research, the VDI 2221 methodology will be carried out in which the design processes are applied to manufacture new systems, such as control improvements, among others. The software Tia Portal and Factory IO were used to visualize the sensors and actuators that simulate the filtering and filling of GW. Finally, it is concluded that the application of a control and automated system for the reuse of GW is of great importance to improve and optimize the use of water and thus reduce water scarcity in different parts of the world.